COVID-19 vaccine acceptance and hesitancy in N'Djamena, Chad: A cross-sectional study of patients, community members, and healthcare workers. - Dylan R Rice; Anatole Balamo; Allah-Rabaye Thierry; Aremadji Gueral; Djerakoula Fidele; Farrah J Mateen; Foksouna Sakadi (Public Library of Science (PLoS), 2022)
As of March 2022, the COVID-19 vaccination rate in Chad approximated 1%. There are no published reports of COVID-19 vaccine hesitancy or beliefs in Chad. We aimed to study COVID-19 vaccine acceptance and hesitancy among community members, patients, and health care workers in urban Chad. We recruited a prospective convenience sample of adult patients, community members, and healthcare workers from N'Djamena, Chad between August-October 2021. Participants completed a 15-minute, 25-question survey instrument exploring demographic, social, and clinical variables related to COVID-19 and an adapted WHO SAGE Vaccine Hesitancy Survey. Primary outcomes were vaccine acceptance and vaccine hesitancy. Regression models were fit to assess associations between Vaccine Hesitancy Scale (VHS) scores, ranging from 10 (least hesitant) to 50 (most hesitant) points, and pre-selected variables of interest. An inductive thematic analysis was used to analyze the qualitative vaccine hesitancy responses. Of 508 participants (32% female; mean age 32 years), 162 were patients, 153 were community members, and 193 were healthcare workers. COVID-19 vaccine acceptance was significantly higher among patients (67%) than community members (44%) or healthcare workers (47%), p < .001. The average VHS score was 29 points (patients = 27.0, community members = 28.9, healthcare workers = 29.4), and more than one-third of participants were classified as highly vaccine hesitant (score >30 points). Knowing someone who died from COVID-19, believing local healthcare workers support vaccination, trusting the government, having a higher socioeconomic status (i.e. having electricity), and reporting medical comorbidities were each associated with less vaccine hesitancy (all p < .05). The vaccine concerns most frequently endorsed were: vaccine side effects (48%), efficacy (38%), safety (34%), concerns about the pharmaceutical industry (27%), and lack of government trust (21%). Four main themes arose from qualitative vaccine hesitancy responses (n = 116): education, trust, clinical concerns, and misinformation and false beliefs. Overall, COVID-19 vaccine acceptance was low, including among health care workers, and reasons for vaccine hesitancy were broad. We detail the most commonly reported concerns of urban Chadians for receiving the COVID-19 vaccine; we also identify subgroups most likely to endorse vaccine hesitancy. These analyses may inform future vaccination outreach campaigns in N'Djamena.